2022
DOI: 10.3390/polym14224860
|View full text |Cite
|
Sign up to set email alerts
|

Box–Behnken Design for Polycarbonate-Pigment Blending: Applications and Characterization Techniques

Abstract: Incorporating pigments into polymers can be done for various purposes, including the introduction of color, interfacial effects, or aesthetics. If these pigments are to disperse properly, then the process of extrusion must be optimized. During polymer compounding extrusion, three effective processing factors were investigated: feed rate (FR), speed (Sp.) and temperature (temp.) for a colored compounded polycarbonate (PC) grade (30/70%). The processing design techniques were obtained by applying design experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Indeed, the present study demonstrates, from the output of the appropriate color, a little deviation is revealed by an optimized set of temperature, feed rate and screw speed values in the context of the processing parameters' specified range. In addition, more research can be performed to determine the optimal processing conditions for various color formulations and grades, leading to a significant reduction in waste [27][28][29][30][31][32].…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the present study demonstrates, from the output of the appropriate color, a little deviation is revealed by an optimized set of temperature, feed rate and screw speed values in the context of the processing parameters' specified range. In addition, more research can be performed to determine the optimal processing conditions for various color formulations and grades, leading to a significant reduction in waste [27][28][29][30][31][32].…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…search can be performed to determine the optimal processing conditions for various c formulations and grades, leading to a significant reduction in waste [27][28][29][30][31][32].…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure6. The extrusion method for the preparation of the film (adapted and recreated from Alsadi et al[36]). …”
mentioning
confidence: 99%